Analysis of Indonesian Shrimp Competition in the World Market Study Case: Thailand, Vietnam, India and China - Meri Berliana; Ke-Chung Peng (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
Shrimp is one of the leading fisheries commodities in Indonesia which is oriented towards international markets with export destinations to some countries. shrimp make a positive contribution to the economy because it generates foreign exchange for the State. This study aims to (1) analyze the percentage growth of the Indonesian shrimp trade in the international market and (2) analyzing the position of competitiveness of Indonesian shrimp in international comparative advantage. This research using time series data in secondary form starting in 1998 until 2017. Data were analyzed using constant market share analysis (CMSA) analyze the percentage growth in Indonesia's shrimp trade in the international market, while to analyze the competitiveness of Indonesian shrimp is the Revealed Comparative Advantage (RCA) comparative advantage approach. The results showed that the factors were significantly affect the growth of the Indonesian shrimp trade viz international shrimp prices, rupiah exchange rates against the dollar and export volume. (1) The growth of Indonesia's shrimp trade can be seen from 1998-2017 with a average percentage of trade growth of 1.5% (2) Based on competitiveness analysis, through Revealed Comparative analysis Advantage (RCA) shows that shrimp export competitiveness Indonesia in the international market has a comparative advantage seen from in 1998-2017 with an average value of RCA> 1 which was 1.04.